Modeling the Survival Time of Trading Companies in the Zachodniopomorskie Voivodship - Markowicz, Iwona (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The aim of this study was to construct models of trading companies’ lifespan, in individual districts of Zachodniopomorskie Voivodship. The author verified whether the impact of the survival time of trading companies on the survival function in general is the same in individual districts. This may inform potential entrepreneurs’ decisions on whether to set up a trading or other company. The Kaplan‑Meier estimator was calculated and a tests verifying similarities of functions of trading companies within the districts was used. Districts were then divided into groups, according to trading companies’ lifespan. Further on, the functions of the intensity of companies’ liquidation for particular districts were analysed. The rankings of districts were compared in terms of the lifespan of trading companies and businesses in total. In the study, the author used REGON registry, containing data about companies established in Zachodniopomorskie Voivodship in 2009–2011. These entities were observed until the end of 2013. It is something to be considered by both decision makers and entrepreneurs, that the probability of liquidation of a trading company is greater than of any other company. Trading activity is prevailing (the highest percentage of all newly established companies are trading companies), however, trading companies are also most in danger of liquidation.